Urbanization and (In)Formalization - Ghani, Ejaz; Kanbur, Ravi (World Bank, Washington, DC, 2013)
Two of the great stylized predictions of development theory, and two of the great expectations of policy makers as indicators of progress in development, are inexorable urbanization and inexorable formalization. Urbanization is indeed happening, beyond the "tipping point" where half the world's population is now urban. However, formalization has slowed down significantly in the past quarter century. Indeed, informality has been increasing. This disconnect raises a number of questions for development analysis and development policy. Is the link between urbanization and formalization more complex than what had been thought? What does this mean for policy? The first core section of this paper asks what exactly is meant by formality and informality. The second core section turns to processes of urbanization and asks how these processes intersect with and interact with the incentives to formalize. The paper examines why cities attract the informal sector and the role that urbanization plays in growth and job creation through both the formal and informal sectors. Cities generate agglomeration benefits in the informal sector, perhaps more so than for the formal sector. The third core section is devoted to policy. At the current conjuncture, agglomeration benefits make a strong case for urbanization as an integral part of development strategy, but concerns about jobless growth and about urban poverty require a focus on the informal sector.